Does the belt and road initiative stimulate China's inbound tourist market? An empirical study using the gravity model with a DID method. Issue 2 (March 2020) - Huang, Xueying; Han, Yuanjun; Gong, Xuhong; Liu, Xiangyan
This study examines the influence of the Belt and Road Initiative on China's inbound tourist market, generated from countries and regions along the Belt and Road, using a gravity model with a difference-in-differences method. Panel data for 2008–2016 indicate that the Belt and Road Initiative has direct and significant positive effects on Chinese international tourist-generating markets, but the annual treatment effects are only partly significantly positive. We also examined the heterogeneous effects and mechanism of the Belt and Road Initiative on the inbound tourist market by grouping countries according to the levels of trade openness with China and economic development. The heterogeneous effect tests reveal that China's international tourist origin countries with low levels of trade openness with China and high levels of economic development benefit from the Belt and Road Initiative. The findings of this study provide policy guidance on expansion for China's inbound tourism market.